PENGARUH DZIKIR RATIB AL-HADDAD TERHADAP KECERDASAN SPIRITUAL DAN EMOSIONAL (LIVING HADIS DI DESA NANGGELA KAB. KUNINGAN) - Alif Kemal Pratama; Hartati Hartati; Ahmad Faqih Hasyim (IAIN Syekh Nurjati Cirebon, 2022)
In carrying out this life to always get peace and tranquility, one solution is to dogood dhikr, dhikr Asmaul Husna, Ratib al-Haddad, blessings of the Prophet, andsome of them. For example, dhikr that can be practiced is to read the dhikr of Ratibal-Haddad. Ratib al-Haddad is a dhikr composed by al Habib 'Abdullah al-Haddadfrom Hadramaut, Yemen. Based on this background, the purpose of this study is tofind out how the living hadith reads Ratib al-Haddad in Nanggela Village, and howthe influence of dhikr ratib al-Haddad on spiritual and emotional intelligence inNanggela Village. This study uses a qualitative method with the reception theoryof living hadith. Sources of data used in this study using primary sources, whosemain subjects include the founder/successor of dhikr ratib al-haddad, ustadz/kiai,village officials, congregations, and the book of ratib al-Haddad. Data collectiontechniques in this study used observation (participants), interviews (free) anddocumentation. In this study, the data analysis technique used to find perfect results begins by studying the data that has been collected both from observations and interviews and also the results after routinely following dhikr ratib al-haddad in Nanggela Village, Kec. Mandirancan Kab. Kuningan. The results of this study indicate that the activities of Ratib al-Haddad in Nanggela Village, Kec. Mandirancan Kab. Kuningan is based on the hadith of the Prophet SAW about the virtue of dhikr as a form of describing the sunnah and habits of the Messenger of Allah. The meaning of reading dhikr Ratib al Haddad has value or essence, which is dhikr increases worship to Allah, can make time more useful during holidays, both studying and working activities so that you can get closer to Allah so that you can reassure the heart. The implementation of the Ratib al-Haddad dhikr is carried out every Monday / Tuesday night after the congregation for the Isha prayer. Not only reading ratib, but in this activity there is also a reading of marhabanan. Ratib alHaddad activities in Nanggela Village, District. Mandirancan Kab. Kuningan has a function to increase the spiritual intelligence of the congregation through reading verses of the Qur'an and increasing dhikr to Allah SWT. The effect of dhikr ratib al-haddad on spiritual intelligence and emotional intelligence can improve mood, peace of mind, peace of mind, and also reduce excessive emotional feelings, and is able to have a positive impact and extraordinary change. This activity is able to increase the spiritual intelligence of the students, so that they feel closer to Allah and feel a more peaceful heart.